2022
DOI: 10.31234/osf.io/982mb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying Error in Effect Size Estimates in Attention, Executive Function and Implicit Learning

Abstract: An accurate quantification of effect sizes for an experimental manipulation has the power to motivate theory, and to reduce misinvestment in scientific resources by informing power calculations during study planning. Such a quantification could theoretically be achieved by a meta-analysis. However a combination of publication bias and small sample sizes (~N = 25) hampers certainty that such an analysis would yield a non-erroneous estimate. We sought to determine the extent to which each of these caveats may pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…28 based on a 2 (single-vs. dual-task condition) x 2 (visual vs. auditory modality) repeated measures ANOVA indicated that results may be inconsistent based on a sample size smaller than 42 (Garner et al, 2022). It is difficult to compare our analyses to this procedure because the experimental designs were quite different, and different statistical methods were used.…”
Section: Predicting Military Multitaskingmentioning
confidence: 98%
“…28 based on a 2 (single-vs. dual-task condition) x 2 (visual vs. auditory modality) repeated measures ANOVA indicated that results may be inconsistent based on a sample size smaller than 42 (Garner et al, 2022). It is difficult to compare our analyses to this procedure because the experimental designs were quite different, and different statistical methods were used.…”
Section: Predicting Military Multitaskingmentioning
confidence: 98%